Resources for the Provision of Nutrition Support to Children in Educational Environments. (December 2017) - Corrigan, Mandy L.; Huang, Shirley; Weaver, Ann; Keeler, David; Rahe, Katina; Balint, Jane; Marti, Michelle; Goodman, Brandis; Nagy, Traci; DeLano, Victoria; Bond, Betty
The use of nutrition support outside of institutional settings has contributed to maintaining the health, well-being, and nutrition status of many medically complex children. As these children grow and enter educational settings, there is a need for awareness of the care that these children require for nutrition support therapy. This document is designed to raise awareness to these needs, provide best practice educational resources for those involved in the supervision or provision of nutrition support to children in an educational environment, and promote safe and effective care. Care of children requiring nutrition support is an ongoing and shared partnership among the educational team, medical team, homecare team, and parents/caregivers. Care is individualized to the specific child and may include provision of nutrition support therapy while in the school setting, maintenance of a nutrition access device, and monitoring to safely prevent or act on signs of potential complications. Suggested roles and responsibilities of those involved with nutrition support care are discussed; however, all interventions and routine care must be in accordance with physician's orders, school nurse privileges and competencies, and state and local regulations.